Role of omega-3 fatty acids in the prevention and treatment of cardiovascular Diseases: A consensus statement from the Experts’ Committee Of National Society Of Cardiometabolic Medicine - Li, Jian-Jun; Dou, Ke-Fei; Zhou, Zhi-Guang; Zhao, Dong; Ye, Ping; Zhao, Jia-Jun; Guo, Li-Xin (Frontiers in Pharmacology, 2022)
Low-density lipoprotein cholesterol (LDL-C) has been considered as the primary target for the prevention and treatment of atherosclerotic cardiovascular disease (ASCVD). However, there are still residual cardiovascular risks in some patients even if LDL-C achieves the target level. Emerging evidence suggestes that elevated triglyceride (TG) level or triglyceride-rich lipoprotein (TRL) cholesterol (TRL-C) is one of the important components of the residual cardiovascular risks. omega-3 fatty acids have been shown to be one of the effective drugs for reducing TG. However, its efficacy in reducing the risk of ASCVD is inconsistent in large randomized clinical trials. There is lack of consensus among Experts regarding the application of omega-3 fatty acids in cardiovascular diseases including heart failure, arrhythmia,cardiomyopathy, hypertension, and sudden death. Hence, the current consensus will comprehensively and scientifically present the detailed knowledge about the omega-3 fatty acids from a variety of aspects to provide a reference for its management of omega-3 fatty acids application in the Chinese population.